The Utilization of Agricultural and Food Industry Wastes as Feed of Grower Pigs in Manokwari Regency West Papua - Widayati, Trisiwi Wahyu; Rahayu, Bernaddeta Wahyuni Irianti; Rahardjo, Dwi Djoko; Santoso, Budi (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2018)
The aim of this study was to find out the potential of agricultural and food industry wastes as the constituents of pig feed to improve pigs’ performance and to reduce the feeding cost. This study was conducted at Manokwari Regency, West Papua Province. The agricultural and food industry wastes were collected from two traditional market, and four small-scale food industries. All materials used as feed were proximately analyzed to determine their nutritional values. Average daily gain, feed consumption and feed coversion ratio were taken to determine the pigs performance. Feed cost using local market prices was estimated in knowing the ability of agricultural and food industry wastes to substitutes commercial feed. The result of this research indicates that the use of agricultural and food industries wastes as an alternative components of pigs’ feed to substitute the commercial feed do not reduce the pigs’ performance and production. Among three feeds that use of agricultural and food industry wastes, feed with the combination of 75% waste and 25% commercial feed had the best feed conversion ratio, namely 2.36. On the other hand, a mixture of 25% wastes and 75% commercial feed was the most economic one, and able to reduce the feeding cost of grower pig up to 48.00%.Key words: agricultural waste, food industry wastes, grower period, pig, feed